Explicit conditions for the nonoscillation of difference equations with several delays - Vera Malygina; Kirill Chudinov (Electronic Journal of Qualitative Theory of Differential Equations, 2013)
We present a sharp explicit condition sufficient for the nonoscillation of solutions to a scalar linear nonautonomous difference equation with several delays.